2017
DOI: 10.1007/s11896-017-9243-z
|View full text |Cite
|
Sign up to set email alerts
|

Planning Ahead? An Exploratory Study of South Korean Investigators’ Beliefs About Their Planning for Investigative Interviews of Suspects

Abstract: Preparation and planning has been argued to be vitally important as to how effectively investigators undertake their interviews with suspects. Yet, it has also been found in previous research that investigators admit that they plan only occasionally, often attributing insufficient time as a reason for not undertaking the task. Employing a novel research paradigm that utilised theoretical foundations concerning planning, the present study explored empirically 95 South Korean financial crime investigators' views… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This suggest that even though policy makers are aware of the consequence of planning and preparation to investigative interview goals (c.f. Kim et al 2018;Walsh and Bull 2010). Their knowledge is domain specific as there is not enough evidence on the impact of pre-interview planning and preparation-by investigators and interpreters, or lack of it, on By contrast, SSA of the engage phase of the PEACE model, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This suggest that even though policy makers are aware of the consequence of planning and preparation to investigative interview goals (c.f. Kim et al 2018;Walsh and Bull 2010). Their knowledge is domain specific as there is not enough evidence on the impact of pre-interview planning and preparation-by investigators and interpreters, or lack of it, on By contrast, SSA of the engage phase of the PEACE model, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It seems appropriate therefore that preparation is an opportunity to advise investigators of such matters, and as such, preparation needs to be embedded as a prerequisite activity. Kim et al (2018) found that such lack of attention to the planning task was associated with organisational culture, and also investigators' own beliefs as to their capability of effectively interviewing without adequate preparation. Walsh and Bull (2010) found that such beliefs by investigators concerning their own skills were misplaced, since their own interviews were actually often poorly planned and prepared, and it was these particular interviews that were often associated with a lack of information yield from interviewees.…”
Section: Interview Planning and Preparationmentioning
confidence: 99%
“…In other words, 'simpler' cases (e.g., volume crime) could impact on whether investigators decide to plan ahead of the interview or not due to the volume of their workload. However, a more recent study found that South Korean police officers' attitudes towards planning were more associated with issues such as organisational culture and investigators' beliefs in their own ability to interview effectively without much planning, rather than with time pressure (Kim et al, 2018). Despite the importance of planning before undertaking investigative interviews, the above barriers could have a significant impact on the overall information gained.…”
Section: Introductionmentioning
confidence: 99%
“…Planning and preparing for an interview is considered an essential step for good practice (Clarke & Milne, 2001;Kim, Walsh, Bull, & Bergstøm, 2017;Leahy-Harland & Bull, 2017;Walsh & Bull, 2010;Walsh & Milne, 2008). The majority of participants in the current study reported that they plan and prepare for an interview.…”
Section: Pre-interview Practicesmentioning
confidence: 99%